Dual paternity in civil birth registration (Research, Society and Development, 2023)
The present study aimed to discuss dual paternity, analyzing the legal requirements and concepts relevant to the theme. The concept of family has changed significantly in recent years, thus breaking with the patriarchal model. According to the Magna Carta of 1988, any institution in which they live together affectionately is recognized as a family unit. Thus, it is considered family, fathers and mothers with blood ties or not. Affiliation, in this regard, becomes equal in rights and obligations, regardless of blood ties. The jurisprudential understanding has been peaceful with regard to the legitimacy of dual paternity on the Birth Certificate, in compliance with the constitutional principle of affectivity. Multiparentality is a reality in current Brazilian society, therefore, the jurisprudential understanding guarantees the right to form families that do not fit the standards, but that have sufficient affective bonds for their constitution. Therefore, the research is bibliographical with a descriptive character, presenting analysis of studies published in the period from 2015 to 2022 and the legislation. It was evidenced in the synthesis of the studies that the dual paternity is a right of the child/adolescent, taking into account the principle of the best interest of the incapable person.